2019
DOI: 10.1186/s13014-019-1352-7
|View full text |Cite
|
Sign up to set email alerts
|

Prospective intra/inter-observer evaluation of pre-brachytherapy cervical cancer tumor width measured in TRUS and MR imaging

Abstract: Background Ultrasound (US) imaging has been proved as an excellent diagnostic tool in gynecology and, due to its wide availability and limited cost, is under intense investigation as base for dose adaptation in cervical cancer brachytherapy. Purpose of this work is to test inter/intra-observer uncertainties between magnetic resonance (MR) and trans-rectal ultrasound (TRUS) imaging in defining maximum tumor width before first brachytherapy (BT) application in a prospective cohort of cervical can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…MRI has been recommended as gold standard imaging for cervical cancer contours, with some comparative studies previously published ( 14 , 23 , 24 ), and for MR-IGABT (repetitive MRI during complete brachytherapy treatment), several studies reported its clinical efficacy for LACC patients in Europe ( 7 , 25 ) and North America ( 26 ). This study aimed to report the treatment outcomes of MR-IGABT for 97 Chinese LACC patients.…”
Section: Discussionmentioning
confidence: 99%
“…MRI has been recommended as gold standard imaging for cervical cancer contours, with some comparative studies previously published ( 14 , 23 , 24 ), and for MR-IGABT (repetitive MRI during complete brachytherapy treatment), several studies reported its clinical efficacy for LACC patients in Europe ( 7 , 25 ) and North America ( 26 ). This study aimed to report the treatment outcomes of MR-IGABT for 97 Chinese LACC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a novel auto-segmentation model that indeed performs comparably well or even better to manual delineation for CTV delineation is desirable. Moreover, the current evaluating performance of segmentation, particularly CTV segmentation, can be challenging due to the large variations among different centers and observers ( 35 , 36 ). Therefore, a three-stage randomized controlled evaluation framework was proposed, combining the three elements of traditional performance metrics, oncologist evaluation, and the Turing imitation test, for a comprehensive assessment of the proposed model in cervical cancer CTV segmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Another prospective comparison study using MRI and transrectal ultrasound images obtained prior to brachytherapy also showed good correlation in maximum tumor width measurements. In this study, a brachytherapy stepper unit was used to acquire the three-dimensional transrectal ultrasound image 15. Although these prospective studies demonstrated ultrasound imaging’s potential in gynecology, it is important to be aware of the technical details under which the studies were conducted in order to properly adapt this technology for application in brachytherapy.…”
Section: Ultrasound Imaging Of Cervical Cancermentioning
confidence: 99%